Design and Realization of Ohmic and Schottky Interfaces for Oxide Electronics. Issue 2 (5th November 2021) - Zhang, Jie; Pai, Yun-Yi; Lapano, Jason; Mazza, Alessandro R.; Lee, Ho Nyung; Moore, Rob G.; Lawrie, Benjamin J.; Ward, T. Zac; Eres, Gyula; Cooper, Valentino R.; Brahlek, Matthew
Abstract : Understanding band alignment and charge transfer at complex oxide interfaces is critical to tailoring and utilizing their diverse functionality. Toward this goal, both Ohmic‐ and Schottky‐like charge transfers at oxide/oxide semiconductor/metal interfaces are designed and experimentally validated. A method for predicting band alignment and charge transfer in ABO3 perovskites is utilized, where previously established rules for simple semiconductors fail. The prototypical systems chosen are the rare class of oxide metals, SrBO3 with B = V–Ta, when interfaced with the multifaceted semiconducting oxide, SrTiO3 . For B = Nb and Ta, it is confirmed that a large accumulation of charge occurs in SrTiO3 due to the higher energy Nb and Ta states relative to Ti. This gives rise to a high mobility metallic interface, which is an ideal epitaxial oxide/oxide Ohmic contact. On the contrary, for B = V, there is no charge transfer into the SrTiO3 interface, which serves as a highly conductive epitaxial gate metal. Going beyond these specific cases, this work opens the door to integrating the vast phenomena of ABO3 perovskites into a wide range of practical devices. Abstract : The diverse functionality of complex oxides can overcome many current technological challenges. Realization, however, necessitates solving the key challenge of tailoring and controlling charge transfer at oxide interfaces. Toward this goal, the authors design and realize both Ohmic‐ and Schottky‐like charge transfers at an important class of oxide/oxide semiconductor/metal interfaces, thus achieving a critical step toward oxide electronics.